Full shut-off of Escherichia coli RNA-polymerase by T7 phage requires a small phage-encoded DNA-binding protein. Issue 13 (9th May 2017) - Tabib-Salazar, Aline; Liu, Bing; Shadrin, Andrey; Burchell, Lynn; Wang, Zhexin; Wang, Zhihao; Goren, Moran G.; Yosef, Ido; Qimron, Udi; Severinov, Konstantin; Matthews, Steve J.; Wigneshweraraj, Sivaramesh
Abstract: Infection of Escherichia coli by the T7 phage leads to rapid and selective inhibition of the bacterial RNA polymerase (RNAP) by the 7 kDa T7 protein Gp2. We describe the identification and functional and structural characterisation of a novel 7 kDa T7 protein, Gp5.7, which adopts a winged helix-turn-helix-like structure and specifically represses transcription initiation from host RNAP-dependent promoters on the phage genome via a mechanism that involves interaction with DNA and the bacterial RNAP. Whereas Gp2 is indispensable for T7 growth in E. coli, we show that Gp5.7 is required for optimal infection outcome. Our findings provide novel insights into how phages fine-tune the activity of the host transcription machinery to ensure both successful and efficient phage progeny development.